INFANTILE CEREBRAL PALSY DEVELOPMENT FACTORS (LITERATURE REVIEW) - V. N. Lokshin; R. B. Isayeva; R. Zh. Seisebayeva; S. A. Abzaliyeva; Sh. K. Sarmuldayeva (Scientific Journal of Pedagogy and Economics, 2019)
The term Infantile Cerebral Palsy refers to complex of chronic neurological disorders that occur during perinatal period because of brain damage. Brain damage can occur in both ante-, intra- and postnatal periods. There are variety of reasons and it is impossible to specify the main one. Damage often occurs before birth, antenatal, during the first 6 months of pregnancy. There are at least three reasons for this: Periventricular leukomalacia (PVL). PVL is a type of lesion that affects alba due to lack of oxygen in the uterus. Abnormal brain development. The lesion may be due to mutations in genes responsible for brain development, some infections, such as toxoplasmosis, parasitic infection, herpes and herpes-like viruses and head trauma. There may be intracranial haemorrhage, when the foetus has a stroke. Haemorrhage may stop blood flow into the vital tissue of the brain, which may cause tissue injury or necrosis. Blood may thicken and damage surrounding tissue. According to various data, intrapartum lesions, such as birth asphyxia or birth trauma, account for up to 42%. In the postnatal period, brain lesion factors with development of cerebral palsy are usually considered infectious, less traumatic ones, but some works mention the hereditary component. Nevertheless, to date, the aetiology of this disease has not been fully studied and it is not clear which pathogenic factors and what conditions lead to cerebral palsy. Therefore, we can state only the multi-aetiology of cerebral palsy and need for greater attention to the study of both biological and environmental factors that have an impact on foetus and new-born.